Kritik dan Dukungan Media Massa terhadap Kebijakan dan Implementasi Akreditasi Sekolah - Prihantoro, Agung (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
The government policy regarding school/madrasah accreditation and its implementation has been reported by mass media. Kompas, as one of the largest mass media outlets in Indonesia, has covered the policy and its implementation in two ways: criticism and support. These reports were analyzed using critical discourse analysis, facilitated by Atlas.ti software. The analysis results indicate that Kompas criticizes the policy and its implementation by featuring critical news articulated by education activists. On other occasions, Kompas supports the policy by directly quoting statements from officials.